POLITENESS STRATEGIES ON DIALOGUE PERFORMED BY DJANGO AND DR. SCHULTZ IN “DJANGO UNCHAINED” MOVIE - PURBA, EMILIYUS MEINRAT (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: Politeness, Face, Politeness Strategies. As a social being, people need to pay attention to the messages conveyed in communication. In verbal communication, people perform politeness that can develop relationship and build cooperation among them. The writer conducted a study about politeness in “Django Unchained” movie which presents about politeness phenomena happening in life aspect at the American slavery era. There are two problems to be solved, they are: (1) What politeness strategies which are mostly used on dialogue performed by Django and Dr. Schultz in “Django Unchained” movie? (2) What factors that influence Django and Dr. Schultz use the strategies which are mostly appeared.This study uses qualitative approach to gather and analyze the data. It is included into document analysis in analyzing and interpreting the utterances on dialogue between Django and Dr. Schultz from the script of the movie to answer the research problem.The result of this study shows that the mostly used politeness strategies is positive politeness strategies with twenty three utterances. In doing politeness strategies, Dr. Schultz is the highest positive politeness user in his utterances to show cooperative will and effort to minimize the social distance with Django. On the other side, Django has a very low frequency in doing the politeness strategies.Based on the results, the writer suggests that the next researchers use other objects reflecting more about performing politeness in daily life also use more theories in analyzing the implicit meanings of the speaker’s utterances.